5.0k views
4 votes
Prove the following identity. Make sure to include all steps taken.
(1+cos\theta )/(sin\theta)+(sin\theta)/(1+cos\theta)=2csc\theta

1 Answer

4 votes

Answer:

See below.

Explanation:


(1+cos(\theta))/(sin(\theta)) +(sin(\theta))/(1+cos(\theta))=2csc(\theta)


((1+cos(\theta))(1+cos(\theta)))/(sin(\theta)((1+cos(\theta))) +((sin(\theta))(sin(\theta)))/((1+cos(\theta))(sin(\theta)))=2csc(\theta)


((1+cos(\theta))(1+cos(\theta))+(sin(\theta))(sin(\theta)))/(sin(\theta)((1+cos(\theta)))=2csc(\theta)


((1+2cos(\theta)+cos^2(\theta)+sin^2(\theta)))/(sin(\theta)(1+cos(\theta))) =2csc(\theta)

Recall the identities:


sin^2(\theta)+cos^2(\theta)=1


(1+2cos(\theta)+1)/(sin(\theta)(1+cos(\theta))) =2csc(\theta)


(2+2cos(\theta))/(sin(\theta)(1+cos(\theta))=2csc(\theta)


(2(1+cos(\theta)))/(sin(\theta)(1+cos(\theta))) =2csc(\theta)


(2)/(sin(\theta)) =2csc(\theta)


2csc(\theta)=2csc(\theta)

User Alex Stockinger
by
5.5k points